2016
DOI: 10.1371/journal.pone.0156677
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Smoking on Pulmonary Tuberculosis in Diabetic and Non-Diabetic Patients

Abstract: BackgroundBoth smoking and diabetes can increase the risk and influence the manifestations and outcomes of tuberculosis (TB). It is not clear whether the influence of smoking on pulmonary TB differs between non-diabetic and diabetic patients. Herein, we assessed the manifestations and outcomes of TB in relation to smoking in both diabetic and non-diabetic TB patients.Methodology/Principal FindingsAll diabetic culture-positive pulmonary TB patients notified from 2005–2010 at three teaching hospitals in Taiwan w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
12
1
1
Order By: Relevance
“…We obtained the same results concerning comorbidities. Our study was not able to confirm the existing evidence that the association of smoking and diabetes increases the risk of developing TB, probably because among our patients, smokers suffering from TB were mostly middle-aged persons who did not suffer from diabetes mellitus [23,25]. Older patients suffering from TB who were treated for diabetes mellitus were rarely smokers.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…We obtained the same results concerning comorbidities. Our study was not able to confirm the existing evidence that the association of smoking and diabetes increases the risk of developing TB, probably because among our patients, smokers suffering from TB were mostly middle-aged persons who did not suffer from diabetes mellitus [23,25]. Older patients suffering from TB who were treated for diabetes mellitus were rarely smokers.…”
Section: Discussioncontrasting
confidence: 89%
“…A significant difference was detected in relation to patients' sex. Smokers suffering from TB were mostly middle-aged men, between 30 and 49 years of age, who were manual laborers [23]. Among the non-smokers, ill with TB were mainly females between 20 and 29 years of age, from the rural environment.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the respondents (n=241, 56.2%) agreed that smoking increases the risk of TB infection, while some confessed they did not know (n=160, 37.3%). According to Bai, Lee, Chien, Suk, and Chiang (2016), TB patients who smoke cigarettes possessed nearly twice the risk of TB infection of non-smokers. In fact, smokers (with TB disease) have a nine times greater risk of mortality than non-smokers (Hutahaean, 2013;Zhang et al, 2019).…”
Section: Statistics and Resultsmentioning
confidence: 99%
“…Smoking has been reported to be significantly associated with positive smear and cavitary pulmonary TB [12], thus may promote transmission of TB [9,10]. Bai et al assessed the manifestations in relation to smoking in both diabetic and non-diabetic TB patients [13]. They reported that the adjusted relative risk of a pretreatment positive smear for a smoker compared with a non-smoker was 2.…”
Section: Smoking and Clinical Manifestations Of Tbmentioning
confidence: 99%
“…Studies have reported that smoking is associated with delayed sputum conversion and unfavorable treatment outcomes [13,14]. Gegia et al reported that current smokers had an increased risk of poor treatment outcome (aRR 1.7; 95% CI: 1.0-2.9) compared with those who had never smoked in Georgia [15].…”
Section: Smoking and Treatment Outcomes Of Tbmentioning
confidence: 99%